Literature Review: Evaluation of Spesific and Non-Spesific Parameters in the Quality Assessment of Rhizome Simplicia - Mars Jenita Grace Santy Indah Purba; Sofi Khoerunnisa; Dini Dwi Oktaviani; Caecilia Sukma Larasati; Yonathan Tri Atmodjo Reubun (STIKes Medistra Indonesia, 2026)
Rhizomes are the underground stems of plants and are widely used as crude drug materials in the Indonesian traditional medicine industry because they contain various beneficial bioactive compounds. Rhizome crude drugs must meet quality standards that can be measured through two groups of parameters—specific and non-specific parameters—to ensure the safety, efficacy, and consistency of these raw materials. This study is a literature review that involves the collection and analysis of secondary data from ten scientific articles obtained through Google Scholar. This study focuses on the evaluation of specific parameters, namely organoleptic properties, water-soluble and ethanol-soluble extract content, as well as phytochemical profiles, and non-specific parameters such as drying loss, moisture content, total ash content, acid-insoluble ash content, and heavy metal content in ten types of rhizome crude drugs: red galangal, yellow turmeric, ginger, red ginger, kencur, purun danau, black temu, temu kunci, mango temu, and wundu watu. Analysis results indicate that Temu Kunci (Kaempferia pandurata Roxb.) has the best overall quality, followed by Red Ginger and Kencur, which each meet all established standards. Conversely, Black Temu and Mango Temu showed non-compliance with non-specific parameters, particularly regarding ash content and moisture content, indicating a need to improve post-harvest processing. Lake Purun requires special attention due to its high heavy metal content, which impacts the aquatic ecosystem in the lake. Standardizing both specific and non-specific parameters is a crucial step to ensure the quality and safety of rhizome crude drugs as raw materials for traditional medicine in Indonesia. Keywords: Herbal Rhizomes, Specific Parameters, Non-Specific Parameters